A Study of Social Consciousness of Senior High School Students Under The Secondary Educational Service Area Office Bangkok 1 and 2 - MUADRAE, AIMJIT; Tosila, Chairat (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
This study aimed to: 1. analyze the alignment between social consciousness and the indicators of the Social Studies, Religion, and Culture curriculum for secondary education, and 2. examine the social consciousness of high school students. The sample consisted of 7 experts and 473 high school students from schools under the Bangkok Metropolitan Secondary Educational Service Area Offices 1 and 2, during the first semester of the 2023 academic year. The research instruments included a 43-item evaluation form to assess the alignment between social consciousness and the curriculum indicators, and a 71-item questionnaire on the social consciousness of senior secondary students. The statistical methods used for data analysis included median, mode, mean, and standard deviation. The findings of the study were as follows: 1. Social consciousness was highly aligned with the indicators of the Social Studies, Religion, and Culture curriculum for senior secondary education, and 2. Senior secondary students exhibited a high level of social consciousness.